Book Reviews. Issue 1 (May 2013) - Carr, Jane
In this section 15 books are reviewed, presented in the following general order: children/family ministry, youth ministry, adult ministry, foundations, teaching-learning process, spirituality/spiritual formation, and leadership/administration—although reviews may not appear for each area. A list of each area and responsible editors appears after the last review in this section. We invite readers to consider reviewing a book for CEJ. Guidelines are available in downloadable documents atwww.biola.edu/cej under Publications Policy on the drop down menu.